2015
DOI: 10.15407/jnpae2015.03.247
|View full text |Cite
|
Sign up to set email alerts
|

137Сs distribution in sod-podzol forest soil of Ukrainian Polissia

Abstract: Житомирський державний технологічний університет, Житомир 2 Київська науково-дослідна станція Українського науково-дослідного інституту лісового господарства і агролісомеліорації ім. Г. М. Висоцького, Лютіж Київської області РОЗПОДІЛ 137 Cs У ДЕРНОВО-ПІДЗОЛИСТИХ ҐРУНТАХ ЛІСІВ ПОЛІССЯ УКРАЇНИ Проведено дослідження щодо розподілу 137 Cs у дерново-підзолистих ґрунтах лісів Полісся України в різних типах лісорослинних умов, з використанням показників питомої активності радіонукліда та щільності радіоактивного забр… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
3
0
5
Order By: Relevance
“…In addition, according to these procedures, soil sampling was made at a depth of 10 cm. Materials of publications [11,12] prove that over time there was migration and redistribution of radionuclides in the deeper soil layers, that is why the above-specified sampling depth does not reflect the current content of radioactive elements in soils. The procedures that were developed for the examination of agricultural lands for radioactive contamination [25,26,33] cannot be used for forest lands.…”
Section: Discussion Of Results Of Improving the Soil Sampling Procedumentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, according to these procedures, soil sampling was made at a depth of 10 cm. Materials of publications [11,12] prove that over time there was migration and redistribution of radionuclides in the deeper soil layers, that is why the above-specified sampling depth does not reflect the current content of radioactive elements in soils. The procedures that were developed for the examination of agricultural lands for radioactive contamination [25,26,33] cannot be used for forest lands.…”
Section: Discussion Of Results Of Improving the Soil Sampling Procedumentioning
confidence: 99%
“…The researchers proposed prognostic models for migration and distribution of radionuclides in soils, but these models had a theoretical basis and were based on the half-life of radioactive elements. Paper [11] studied the distribution of 137 Cs in soddy podzolic soils in different types of forest-vegetative conditions. The authors found that the forest litter remains a geochemical barrier on the way of radionuclide migration in soil, and maximum magnitudes of the specific activity of radionuclide were found in the humus-eluvial horizon.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Дослідники відмічали значну акумулюючу роль лісових рослин та варі-ювання показника інтенсивності надходження 137 Cs до різних видів у межах одного і того самого екотопу, широкий діапазон рівнів їхнього радіоактивного забруднення та важливу роль у перерозподілі радіонуклідів у лісових біогеоценозах [1,7,11,17,18,20,24,27]. У перші 10-20 років після аварії на ЧАЕС з'явилася достатня кількість публікацій [5,11,20,23,26,28], у яких описано основні фактори, що впливають на інтенсивність накопичення радіонуклідів рослинами: систематичне положення, життєва форма, утворення симбіозу з мікоризою грибів, глибина розміщення кореневої системи у ґрунті, тип ґрунту, мінералогічний та гранулометричний склад ґрунту, багатство (кількість мінерального азоту), вологість, кислотність (рН), вміст органічної речовини, вміст обмінних К + і Са 2+ , ізотопний склад радіоактивних випадінь, їхні фізико-хімічні властивості, форма і шлях надходження радіонуклідів до екосистеми.…”
Section: вступunclassified
“…Натепер основним шляхом надходження радіонуклідів у рослини є кореневий. Доведено, що інтенсивність надходження 137 Cs та 90 Sr з ґрунту в рослини різних видів прямо залежить від вертикального розподілу радіонуклідів та інтенсивності кореневої діяльності рослин по профілю ґрунту [9,12,14,23]. Чим глибше розміщується коренева система рослин, тим меншим є надходження радіонуклідів до наземної фітомаси.…”
Section: вступunclassified